Paleo-environmental conditions of the Early Cambrian Niutitang Formation in the Fenggang area, the southwestern margin of the Yangtze Platform, southern China: Evidence from major elements, trace elements and other proxies. (15th June 2018) - Li, Jin; Tang, Shuheng; Zhang, Songhang; Xi, Zhaodong; Yang, Ning; Yang, Guoqiao; Li, Lei; Li, Yanpeng
Graphical abstract: Highlights: Marine productivity tends to be consistent during deposition of the Niutiang Formation, although production may increase sharply with the influence of sedimentary events. Mo-U systematics indicate Fe-Mn cycling via redox oscillation and diagenetic re-oxidization via bioactivities or resuspension, which provide a unique insight to environmental change and biological diversification in the Early Cambrian Yangtze sea. The paleo-environmental model in Early Cambria Yangtze sea that progressive transition from anoxic deep waters with euxinic episodes to oxic conditions can be inferred via geochemistry analysis. Abstract: The Precambrian/Cambrian transition was a key time in Earth history, especially for marine biological evolution and oceanic chemistry. The redox-stratification with oxic shallow water and anoxic (even euxinic) deeper water in the Early Cambrian Yangtze Sea, which gradually became completely oxygenated, has been suggested as a possible trigger for the "Cambrian explosion" of biological diversity. However, for some areas in northern Guizhou where the exploration and research are lacking, identifying this pattern of redox-stratification by paleo-environmental analysis from borehole data is still in need. Here, we report a remarkable variation range in trace elements (Mo, V, U, Ni, Th, Co, Sc, Zn and Cu), molar Corg :P ratios and pyrite morphology from 27 core samples from one new drill hole (XY1, located in the Fenggang area, northern Guizhou) on the Yangtze Platform, South China. High levels of Ba (from 3242 ppm to 33, 800 ppm) and total organic carbon (TOC; from 4% to 9.36%) in 15 core samples in the Lower Member (LM) of the Niutitang Formation indicated elevated primary productivity in the study area. Redox change was recorded based on enrichment factors (EFs) for RSTEs (Mo, U, and V), redox proxies (V/(V + Ni), Ni/Co, V/Sc and Th/U), Corg :P ratios and particle size of framboidal pyrite. These signatures demonstrate that the LM was deposited under anoxic conditions with sulfidic episodes, whereas the Upper Member (UM) of the Niutitang Formation was deposited under suboxic/oxic conditions with intermittently anoxic episodes. Mo/TOC ratios (from 3.72 to 39.86, mean 18.76) suggest weak-moderate water mass restriction. Mo-U covariation patterns (strong but variable enrichment of Mo and U; MoEF ranging from 31.45 to 257.97; UEF ranging from 4.68 to 39.07) in the LM show alternation of particulate shuttling and redox conditions occurred in the Early Cambrian Yangtze Sea, whereas Mo-U covariation patterns (moderate Mo enrichment but depletion or non-enrichment of U; mean MoEF : 7.29; mean UEF : 0.95) in the UM may indicate the combined influence of particulate shuttling and diagenetic diffusion of U via bioactivities, which result in low U values and an anoxic signature from frambiodal pyrite particle size (mean: 4.556 μm; median: 4.41 μm). Additionally, excess Ba (Baxs ) concentration (33, 800 ppm and 32, 500 ppm) and association patterns of trace-metal enrichment in the LM indicate the existence of submarine hydrothermal events. In addition, during deposition of the UM, bioactivities indicated by Mo-U systematics and oxic conditions indicated by redox sensitive trace elements (RSTEs) and multiple-proxies, may be a cause of biological diversification recorded in the Early Cambrian. Finally, data in this record a progressive transition from anoxic bottom waters with euxinic episodes to overwhelming oxic conditions during Early Cambrian.